PETROLOGY AND GEOCHEMISTRY OF WEST PHILIPPINE BASIN BASALTS AND EARLY PALAU-KYUSHU ARC VOLCANIC CLASTS FROM ODP LEG 195, SITE 1201D: IMPLICATIONS FOR THE EARLY HISTORY OF THE IZU-BONIN-MARIANA ARC - Savov I.P.; Hickey-vargas R.; Dantonio M.; Ryan J.G.; Spadea P. (My University, 2006)
Site 1201D of Ocean Drilling Program Leg 195 recovered basaltic and volcaniclastic units from the West Philippine Basin that document the earliest history of the Izu–Bonin–Mariana convergent margin. The stratigraphic section recovered at Site 1201D includes 90?m of pillow basalts, representing the West Philippine Basin basement, overlain by 459?m of volcaniclastic turbidites that formed from detritus shed from the Eocene–Oligocene proto-Izu–Bonin–Mariana island arc. Basement basalts are normal mid-ocean ridge basalt (N-MORB), based on their abundances of immobile trace elements, although fluid-mobile elements are enriched, similar to back-arc basin basalts (BABB). Sr, Nd, Pb and Hf isotopic compositions of the basement basalts are similar to those of basalts from other West Philippine Basin locations, and show an overall Indian Ocean MORB signature, marked by high 208Pb/204Pb for a given 206Pb/204Pb and high 176Hf/177Hf for a given 143Nd/144Nd. Trace element and isotopic differences between the basement and overlying arc-derived volcaniclastics are best explained by the addition of subducted sediment or sediment melt, together with hydrous fluids from subducted oceanic crust, into the mantle source of the arc lavas. In contrast to tectonic models suggesting that a mantle hotspot was a source of heat for the early Izu–Bonin–Mariana arc magmatism, the geochemical data do not support an enriched, ocean island basalt (OIB)-like source for either the basement basalts or the arc volcanic section.
Keywords: back-arc basalts; Izu–Bonin–Marianas; Philippine Sea; subduction initiation; Ocean Drilling Program Leg 195; Кайнозой::Палеоген::Олигоцен; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Oligocene; Cenozoic::Paleogene::Eocene